1968
DOI: 10.1103/physrev.166.1136
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear-Structure Studies ofSr88andY89by Inelastic Electron Sca

Abstract: The nuclei Sr 88 and Y 89 have been studied by observing the inelastic scattering of 65-and 70-MeV electrons through angles 70°-150°, with an over-all energy resolution of 200 keV. Strongly excited states were found in 4.16 MeV. The data were analyzed by a distorted-wave calculation to determine multipolarities and reduced nuclear radiative transition probabilities. The results show that the excited states in Y 89 cannot be described by a weak coupling of the 2pi/2 proton to core-excited states of Sr 88 . The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1968
1968
1989
1989

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…The results for the 7-ray energies observed in this work are listed in Table III, where the relatively large errors appearing on some 7-ray transitions reflect Doppler broadening arising from the short lifetimes of the states. 8 Table IV shows the 40 Ca excitation energies compiled by Endt and van der Leun, 9 the recently reported results of Armini et al 6 results for the energy of the T-1 analog to the 40 Sc ground state is shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The results for the 7-ray energies observed in this work are listed in Table III, where the relatively large errors appearing on some 7-ray transitions reflect Doppler broadening arising from the short lifetimes of the states. 8 Table IV shows the 40 Ca excitation energies compiled by Endt and van der Leun, 9 the recently reported results of Armini et al 6 results for the energy of the T-1 analog to the 40 Sc ground state is shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 93%
“…The development of Ge(Li) detectors has made y-ray measurements an ideal method for determining the energies of certain analog levels. A number of authors [3][4][5][6] have used such techniques to obtain the energy of the lowest T=l level of 40 Ca, and a 41 K( 3 He,d) 40 Ca charged-particle spectrograph result of comparable accuracy has also been reported. 7 Since Armini, Sunier, and Richardson, 6 whose result for that level is E x = 7669.1 ±3.3, have questioned the precision of the Berg and Kashy 5 value of E x = 7660.8±1.2, and in view of the significant difference between the two results, the present work was undertaken.…”
Section: Introductionmentioning
confidence: 93%
“…Mit der yon Helm [23] angegebenen mittleren Lebensdauer z~(E3)= 1,08 9 10-10 sec des 3--Niveaus fiir den 7-Obergang in den Grundzustand und dem Verzweigungsverh/iltnis der l~lbergangswahrscheinlichkeiten Hw(E1 ) Shastry [19] 2,5 9 1012 2,84.1012 2,68 9 1012 Ragaini [22] 3,8 9 10 -3 Perdrisat [21] 1,7 9 1012 1,2-10 -3 W/ihrend die Berechnung der Obergangsgr6Ben des E1-Oberganges yon 88Sr bisher allein auf die Ergebnisse inelastischer Streuexperimente [14,23] zurtickgeht, ist im Falle eines E1-Oberganges nach Pauli und Alder [24] auch eine Aussage fiber den ,,hindrance"-Faktor Hw(E1 ) aus der Gr613e des ,,penetration"-Parameters ~/ m6glich. Fig.…”
Section: Diskussionunclassified
“…The y-rays following the decay of 17.8-min 88 Rb and the level scheme of 88 Sr has been well characterised as a result of /3^-decay studies as well as numerous reaction studies of the levels of 88 Sr [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Two of the most recent studies of 88 Rb decay are those of RAGAINI and MEYER [8] and of BUNTING [9], RAGAINI and MEYER [8] in an attempt to resolve the ambiguities existing in the previous works.…”
Section: Introductionmentioning
confidence: 99%